Pengaruh suplementasi besi-folat, vitamin A dan seng terhadap durasi dan frekuensi sakit ISPA pada anak sekolah dasar dengan status gizi kurang di Kabupaten Bantul - Sri Mulyati; Madarina Julia; Abidillah Mursyid (Jurnal Gizi Klinik Indonesia, 2007)
Background: Children in school-age are categorized as sensitive group who are in the second fast growth so that adequate nutrition intake is needed. Under-nourished students tend to have low immune and susceptible to illness. Nutrition with infections disease has reciprocal relation, well-nourished will increase body immunity to infections disease and on the other hand, infection disease may worsen nutritional status condition. The relation between lack of micro-nutrient and the decreasing of body immune to ARI need to be solved; one way to solve such problem is by giving supplementation.Objective: The study was meant to know the influence of iron-folate, vitamin A and zinc supplementation to the duration and frequency of ARI among under-nourished elementary students grade IV – VI in Bantul regency.Method: This was experimental with factorial design. Subjects were divided into four treatment groups: iron-folate supple-mentation group were 38 students, iron-folate and vitamin A supplementation group were 39 students, iron-folate and zinc supplementation group were 40 students, and iron-folate, vitamin A and zinc supplementation group were 37 students. Data collected with recall twice a week during 3 months supplementation.Result: Supplementation did not influence frequency of ARI among 113 elementary students with ARI (p=0.72) among four supplementation groups, while the duration of ARI were: iron-folate, vitamin A, zinc 6.5 days, iron-folate, vitamin A 7.7 days, iron-folate, zinc 8.6 days and iron-folate only 11.2 days. In the average, the duration of ARI from every ARI symptom was the duration of cough, the longest cold was in iron-folate group, while cough symptom, the shortest cold was in iron-folate, zinc and vitamin A group.Conclusion: There were influence differences between iron-folate supplementation with Vitamin A and/or zinc and iron-folate supplementation to ISPA duration, but it did not give smaller influence statistically among frequency of ARI. Students with iron-folate, zinc and vitamin A supplementation had the shortest duration of ARI while students with iron-folate supplementation had the longest duration of ARI.